Permeability of porcine blood brain barrier to somatostatin analogues - Fricker, Gert; Nobmann, Stephanie; Miller, David S. (British journal of pharmacology, 2002)
Transport of a fluorescent somatostatin analogue (NBD-octreotide) across freshly isolated functionally intact capillaries from porcine brain was visualized by confocal microscopy and quantitated by image analysis. Luminal accumulation of NBD-octreotide showed all characteristics of specific and energy-dependent transport. Steady-state luminal fluorescence averaged 2 - 3 times cellular fluorescence and was reduced to cellular levels when metabolism was inhibited by NaCN. The accumulation of NBD-octreotide in capillary lumens was inhibited in a concentration-dependent manner by unlabelled octreotide, by verapamil, PSC-833 and cyclosporin A, potent inhibitors of p-glycoprotein, and by leucotriene C4, a strong modulator of Mrp2. Conversely, unlabelled octreotide reduced luminal accumulation of fluorescent BODIPY-verapamil on p-glycoprotein and of fluorescein-methotrexate, on Mrp2. None of the inhibitors used significantly reduced cellular accumulation of the fluorescent substrates. Together, the data are consistent with octreotide being transported across the luminal membrane of porcine brain capillaries by both P-gp and Mrp2, providing further evidence that both transporters contribute substantially to the active barrier function of this endothelium.
Gesehen am 25.04.2017